Clinical and socio-environmental determinants of multidrug-resistant vibrio cholerae 01 in older children and adults in Bangladesh. (April 2021) - Garbern, Stephanie C.; Chu, Tzu-Chun; Yang, Phillip; Gainey, Monique; Nasrin, Sabiha; Kanekar, Samika; Qu, Kexin; Nelson, Eric J.; Leung, Daniel T.; Ahmed, Dilruba; Schmid, Christopher H.; Alam, Nur H.; et al.
Highlights: Multidrug resistant (MDR) Vibrio cholerae O1 is a major public health concern. 28.1% of Vibrio cholerae O1 were MDR in population >5 years of age in urban Bangladesh. Antimicrobial susceptibility of Vibrio cholerae O1 fluctuates rapidly over time. Multiple clinical and socio-environmental risk factors are associated with MDR. Prior antibiotic use is a significant risk factor for MDR. Abstract: Objectives: Few studies have evaluated determinants of multidrug-resistant (MDR) Vibrio cholerae O1 in older children and adults. This study aimed to characterize the prevalence of MDR V. cholerae O1 and associated risk factors among patients over five years of age in Bangladesh. Methods: Stool culture and antimicrobial susceptibility testing were performed as a part of a larger study at Dhaka Hospital in Bangladesh from March 2019–March 2020. Univariate statistics and multiple logistic regression were used to assess the association between a range of variables and MDR V. cholerae O1. Results: MDR was found in 175 of 623 (28.1%) V. cholerae O1 isolates. High levels of resistance were found to erythromycin (99.2%), trimethoprim-sulfamethoxazole (99.7%), and ampicillin (88.9%), while susceptibility was high to tetracyclines (99.7%), azithromycin (99.2%), ciprofloxacin (99.8%), and cephalosporins (98.6%). MDR was associated with prior antibiotic use, longer transport time to hospital, higher income, non-flush toilet use, greater stool frequency, lower blood pressure, lower mid-upper arm circumference, and lower percent dehydration. Conclusions: MDR V. cholerae O1 was common among patients over five in an urban hospital in Bangladesh. Significant factors associated with MDR may be actionable in identifying patients with a high likelihood of MDR.